Nasopharyngeal Carriage of Pneumococcus in Children in England up to 10 Years After 13-Valent Pneumococcal Conjugate Vaccine Introduction: Persistence of Serotypes 3 and 19A and Emergence of 7C. (21st September 2022) - Tiley, Karen S; Ratcliffe, Helen; Voysey, Merryn; Jefferies, Kimberley; Sinclair, Gemma; Carr, Melanie; Colin-Jones, Rachel; Smith, David; Bowman, Jaclyn; Hart, Thomas; Kandasamy, Rama; Hinds, Jason; et al.
Abstract: Background: Monitoring changes in pharyngeal carriage of pneumococcus in children following 13-valent pneumococcal conjugate vaccine (PCV13) introduction in the United Kingdom in 2010 informs understanding of patterns of invasive pneumococcal disease (IPD) incidence. Methods: Nasopharyngeal swabs from healthy children vaccinated with PCV13 according to schedule (2, 4, and 12 months) were cultured and serotyped. Results for children aged 13–48 months were compared between 2014–2015 and 2017–2019 and with children aged 6–12 months (2017–2020). Blood was obtained from a subset of children for pneumococcal serotype-specific immunoglobulin G (IgG). Results: Total pneumococcal carriage at 13–48 months was 47.9% (473/988) in 2014–2015 and 51.8% (412/795) in 2017–2019 ( P = .10); at age 6–12 months this value was 44.6% (274/615). In 2017–2019, 2.9% (95% confidence interval, 1.8%–4.3%) of children aged 13–48 months carried PCV13 serotypes (mainly 3 [1.5%] and 19A [0.8%]) and >20% carried the additional 20-valent PCV (PCV20) serotypes. Similar proportions of children had IgG ≥0.35 IU/mL for each serotype in 2014–2015 and 2017–2019. Serotype 7C carriage increased significantly ( P < .01) between 2014–2015 and 2017–2019. Carriage of PCV20 serotypes 8 and 12F, both major causes of IPD, was rare. Conclusions: Introduction of PCV20, if licensed for children, could significantly change the composition of pneumococcal serotypes carried in the pharynx of UK children. Clinical Trials Registration: NCT03102840. Abstract : Pneumococcal carriage in children aged 13–48 months remained stable between 2014–2015 and 2017–2019, both overall and for individual serotypes, with the exception of an increase in serotype 7C. More than 20% of children carried the additional serotypes contained in PCV20.